A Biopolymer Chitosan and Its Derivatives as Promising Antimicrobial Agents against Plant Pathogens and Their Applications in Crop Protection. (19th June 2011) - Badawy, Mohamed E. I.; Rabea, Entsar I.
Abstract : Recently, much attention has been paid to chitosan as a potential polysaccharide resource. Although several efforts have been reported to prepare functional derivatives of chitosan by chemical modifications, few attained their antimicrobial activity against plant pathogens. The present paper aims to present an overview of the antimicrobial effects, mechanisms, and applications of a biopolymer chitosan and its derivatives in crop protection. In addition, this paper takes a closer look at the physiochemical properties and chemical modifications of chitosan molecule. The recent growth in this field and the latest research papers published will be introduced and discussed.